Pelaksanaan Bantuan Hukum Secara Cuma-Cuma (Pro Bono) Pada DPC Peradi Rumah Bersama Advokat (RBA) Kabupaten Malang - Maharani Putri Laimeheriwa; Hermanto Silalahi; Celina Tri Siwi K (Comprehensive Law Journal, 2024)
This research aims to find out how pro bono obstacles providing free or pro bono legal assistance to the community is implemented and what are the experienced by the DPC PERADI Rumah Bersama Advokat (RBA) Malang Regency. The research method used empirical juridical research with a qualitative approach. Data sources were collected through interviews on informants consisting of the Chair and Secretary of Peradi RBA Malang Regency, and library data obtained from library sources, statutory regulations, and other literature. The results of the research show that Peradi RBA Malang Regency is pro bono legal assistance to the community has gone well and there were 6 (six) cases successfully handled in the period of 2021 to 2023. Peradi RBA Malang Regency also collaborates with various agencies to show the public that this organization exists to help underprivileged people obtain their rights. The obstacles faced in providing pro bono legal assistance are time, cost and bad stigma from society. Therefore, education for the public by the government and law enforcement officials must be a concern, because this education is very necessary to protect the rights of the community itself.